Quality-adjusted assessment and determinants of midwife-delivered antenatal care performance in primary health services: Evidence from Indonesia - Tilaili Ibrahim; Maimun Syukri; Hizir Sofyan; Nurjannah Nurjannah (Narra Sains Indonesia, 2026)
Indonesia continues to face a high maternal mortality rate despite improvements in maternal health service coverage. Antenatal care (ANC) performance is commonly evaluated using service coverage indicators, such as first antenatal visit (K1) and fourth antenatal visit (K4). However, these indicators do not fully capture the quality of care delivered during ANC contacts. The aim of this study was to assess ANC implementation based on the Indonesian Ministry of Health 10T Standard (10T), develop quality-adjusted performance indicators integrating coverage and service quality, and identify factors associated with midwife performance in primary health services. A cross-sectional study was conducted among village midwives in Banda Aceh, Indonesia. ANC quality was assessed using 37 indicators derived from the 10T Standard, while midwife performance was evaluated using conventional coverage indicators and newly modified quality-adjusted indicators, namely modified K1 (K1mod) and modified K4 (K4mod). Individual, organizational, and psychological determinants of performance were analyzed using structural equation modeling (SEM). The results indicated that conventional ANC coverage was high, with mean K1 and K4 values of 99.61% and 91.51%, respectively. However, after adjustment for 10T implementation, performance declined substantially to 84.89% for K1mod and 77.94% for K4mod, indicating that coverage-based indicators overestimated actual performance. Implementation of the 10T Standard varied across components: medical identity recording (95.4±5.7%), medical examination (90.6±8.1%), and intervention (87.6±10.7%) were relatively well implemented, whereas some components, such as counseling or health education and nutritional assessment, were less consistently performed. Key gaps were observed in nutritional assessment. SEM showed acceptable model fit (RMSEA=0.038; GFI=0.971; AGFI=0.939; TLI=0.964; CFI=0.981). Organizational factors had the strongest direct effect on midwife performance (β=0.361, p<0.001) and ANC quality (β=0.310, p<0.001), followed by individual and psychological factors. ANC quality also had a significant direct effect on midwife performance (β=0.388, p<0.001) and mediated the effects of individual, organizational, and psychological factors. These findings indicate that high ANC coverage does not necessarily reflect high-quality service delivery. Quality-adjusted indicators provide a more comprehensive measure of midwife performance, and strengthening organizational support, particularly resources, leadership, and incentives, is essential to improve ANC quality and performance in primary health services.